Polanyian Perspectives on Instituted Economic Processes, Development and Transformation: Introduction - Ramlogan, Ronnie; Harvey, Mark (International Review of Sociology, 2003)
Focuses on the presentation 'Polanyian Perspectives on Instituted Economic Processes, Development and Transformation' at an international workshop held at Manchester, Connecticut. Organizer of the workshop; Theme of the workshop. The workshop was organized by the Centre for Research on Innovation and Competition. The article discusses varieties of capitalism, supply and demand, price formation, competition, economic motives, market economy, and the book "The Great Transformation," by Karl Polyani.
Keywords: Connecticut; Great Transformation, The (Book); Manchester Conn.; POLANYI, Karl, 1886-1964; United States; capitalism; competition; supply and demand; workshops (adult education)